2023
DOI: 10.1161/strokeaha.122.041606
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Thrombus Volume and Interaction With First-Line Endovascular Treatment Device Choice

Abstract: Background: A larger thrombus in patients with acute ischemic stroke might result in more complex endovascular treatment procedures, resulting in poorer patient outcomes. Current evidence on thrombus volume and length related to procedural and functional outcomes remains contradicting. This study aimed to assess the prognostic value of thrombus volume and thrombus length and whether this relationship differs between first-line stent retrievers and aspiration devices for endovascular treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…We found a significant association between the thrombus volume and functional outcome in the Registry population. This association was also reported by Baek et al (2017) [ 22 ] and van Voorst et al (2023) [ 9 ], but it was not found by Borst et al (2017) [ 23 ]. Unlike Baek et al (2017) [ 22 ], we did not find a significant association between the thrombus volume and successful reperfusion.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…We found a significant association between the thrombus volume and functional outcome in the Registry population. This association was also reported by Baek et al (2017) [ 22 ] and van Voorst et al (2023) [ 9 ], but it was not found by Borst et al (2017) [ 23 ]. Unlike Baek et al (2017) [ 22 ], we did not find a significant association between the thrombus volume and successful reperfusion.…”
Section: Discussionsupporting
confidence: 79%
“…Imaging characteristics, on the other hand, are more rapidly and consistently available and contain pertinent information about the patient’s present condition. In LVO stroke patients, certain radiological imaging characteristics of the thrombus on CT scans, such as length, volume, perviousness, and density, have been shown to be related to various outcome measures of stroke treatment [ 5 , 6 , 7 , 8 , 9 , 10 ]. However, thrombus location is the only thrombus imaging characteristic that is currently taken into account during the triage of ischemic stroke patients [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…16 A recent analysis of the MR CLEAN registry performed manual segmentations and measurements of thrombi using a 3-dimensional imaging software. 17 Larger volume thrombi were associated with a lower probability of functional independence defined as a modified Rankin Scale score ≤2 (odds ratio [OR], 0.78 [95% CI, 0.64-0.96]) and a higher number of retrieval attempts (OR, 0.16 [95% CI, 0.04-0.28]). 18 A recent study by Santo et al 19…”
Section: Clot Analysis and Characterizationmentioning
confidence: 99%
“…An in-vitro study showed that the combined technique achieved the highest success rates in removing stiff, calcified clots [17]. Consequently, determining clot pathology prior to MT could be useful for selecting the most effective initial treatment strategy [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%